Anxiety, depression, professional fulfilment and burnout: Public and private doctors' differential response to CoVID-19 pandemic - Virendra V Singh; Bikram K Dutta; Ankit Singhal; Priyadarshee Patra; Anindya K Gupta; Raghu N Mani (Industrial Psychiatry Journal, 2023)
Introduction: Covid-19 pandemic has been a challenge for healthcare system; the doctors in public and private setups are at the center of this challenge. Public and private doctors differ in personality and some occupational aspects. Do these differences reflect in their response to Covid? Aim: To study the difference in anxiety, depression, burnout, and professional fulfillment between doctors in public and private setup during Covid-19 second wave and to assess their coping strategies. Methods: A cross-sectional Internet-based observational study was conducted using Stanford PFI, GAD-7, PHQ-2, BFI-10, and brief COPE questionnaires. Results: A total of 114 public and 37 private doctors participated in the study. Doctors in private were older in age and deferred in personality profile. Significantly, more private doctors screened for anxiety disorder. 62.2% of private and 41.2% public doctors felt professionally fulfilled. Burnout and depression were not significantly different between groups. Active coping, acceptance, and planning coping were significantly more used by private doctors. Conclusion: There are differences how doctors in different setups respond to Covid-19, and there is need to understand these factors.